Allergic Rhinitis and Its Impact on Asthma in Asia Pacific and the ARIA Update 2008 - Pawankar, Ruby (World Allergy Organization Journal, 2012)
The prevalence of allergic diseases such as allergic rhinitis (AR) and asthma are markedly increasing to epidemic proportions worldwide as societies adopt Western lifestyles. An estimated 300 million persons worldwide have asthma, about 50% of whom live in developing countries, and about 400 million people suffer from AR. AR has a marked impact on quality of life, socially, at school, and in the workplace and is a huge socioeconomic burden. Thus, there was clearly a need for a global evidence-based guideline not only for managing AR but also highlighting the interactions between the upper and lower airways including diagnosis, epidemiology, common risk factors, management, and prevention. The Allergic Rhinitis and its Impact on Asthma (ARIA) document was first published in 2001 as a state-of-the-art document for the specialist, the general practitioner, and other health care professionals. Subsequent research and increasing knowledge have resulted in the ARIA 2008 update. The present review summarizes the ARIA update with particular emphasis on the current status of AR and asthma in Asia Pacific.